Concerns and considerations for parents and coaches - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
This chapter explores key concerns and considerations for parents and coaches when dealing with young athletes at the start of their journey. First, understanding how to place appropriate demands on young athletes is an important consideration for coaches and parents. It is widely understood that high-quality and challenging experiences, as opposed to high quantity, are critical developmental tools. However, because of the dynamic and individualised nature of development, individualised needs (rather than just chronological organisation) must be recognised. Guidelines to ensure this individualised approach are presented. Finally, the important of the parent relationship during this key stage is presented and suggestions about how to ensure the child benefits from a degree of challenge, rather than the parent acting as a `snowplough`, are offered. The final section will examine how effective Talent Development Environment (TDEs) should equip young athletes with the early experiences to facilitate this non-linear development (and the consequences of failing to do so).